Effect of low-dose primaquine treatment on Plasmodium vivax recurrence and transmission-blocking activity in southwest Ethiopia: a longitudinal cohort study - Hallelujah Getachew; Kassahun Habtamu; Ashenafi Abossie; Assalif Demissew; Arega Tsegaye; Teshome Degefa; Daibin Zhong; Xiaoming Wang; Guofa Zhou; MingChieh Lee; James W. Kazura; Christopher L. King; et al. (Malaria Journal)
Abstract Background Existing malaria control strategies for Plasmodium vivax are challenging due to its dormant and relapsing liver stages, as well as the early onset of gametocytogenesis. Primaquine (PQ) effectively eliminates dormant stages and can kill gametocytes; however, it necessitates repeated dosing. In this study, the effectiveness of chloroquine (CQ) plus low-dose of PQ on recurrence and its transmission-blocking activity was evaluated. Methods Between September 2019 and July 2022, a prospective cohort study was conducted in the Jimma-Arjo and Dabo-Hanna districts of the Oromia region in Ethiopia. A total of 214 uncomplicated cases of P. vivax malaria were enrolled in the study. Participants were treated with either CQ alone (106) or CQ + PQ (108), based on whether their district was targeted for P. vivax elimination by the national malaria programme or not. After enrolment, participants were followed for clinical illness and parasitaemia on days 28, 42, and monthly for one year. To assess the effect of different treatment regimens on transmission-blocking activity, Anopheles arabiensis mosquitoes were used in direct membrane-feeding assays (DMFA) at baseline (pre-treatment) and on day 42 (post-treatment). Based on polymerase chain reaction (PCR) positivity, the time to the first recurrence was estimated using Kaplan–Meier survival analysis. Cox regression models were employed to assess risk factors for recurrence. Results Of 3,590 individuals screened for malaria, 323 tested positive for P. vivax, and 214 were enrolled. Of these, 98.6% (211/214) completed the day 28 follow-up, and 67.3% (144/214) completed the one-year follow-up. Between days 28 and 42, 24% (95% CI 15.8–32.2%) of those individuals receiving CQ alone were PCR positive, and 10.3% (95% CI 4.5–16.0%) in those receiving CQ plus PQ. This represented a 57.3% reduction P. vivax recurrence in the CQ + PQ treatment group compared to CQ alone (risk ratio = 0.427, 95% CI 0.222–0.824, p = 0.008). During the year of follow-up at least one recurrence occurred in 70% (95% CI 59.1–80.2%) of the CQ alone and 46% (95% CI 35.5–58.1%) in the CQ + PQ treatment group (p < 0.001). Treatment regimen, high baseline parasitaemia and presence of gametocytaemia were risk factors for P. vivax recurrence. Compared to baseline DMFA at day 42, individuals showed an inhibition intensity of 39.0% in the CQ alone versus 77.8% in the CQ + PQ treatment group (p = 0.016), while inhibition prevalence was 35.2% in the CQ alone and 70.1% in the CQ + PQ treatment group (p = 0.021). Conclusions This study demonstrate that with limited supervision of CQ + PQ treatment significantly lowers the risk of P. vivax recurrence in health clinics of southwest Ethiopia compared to CQ alone. Adding PQ to CQ also reduced P. vivax transmission to mosquito vectors relative to CQ alone but did not result in a complete transmission-blocking effect by day 42 post-treatment. Therefore, improved health education on treatment adherence and bed net use could enhance the effectiveness of PQ plus CQ. Higher doses of PQ for a shorter duration may be necessary to enhance treatment adherence, reduce recurrence rates, and decrease the risk of transmission.